Starfish Gonadotropic Hormone: From Gamete-Shedding Substance to Relaxin-Like Gonad-Stimulating Peptide - Mita, Masatoshi (Frontiers in Endocrinology, 2019)
The first report of a gonadotropic substance in an invertebrate hot-water extract of radial nerve cords from starfish Asterias forbesi that induced the shedding of gametes when injected into the coelomic cavity in a ripe individual occurred in 1959. The active substance was named gamete-shedding substance (GSS) or radial nerve factor. GSS is the primary mediator of oocyte maturation and ovulation in starfish. However, the effect of gamete-shedding substance is indirect. Resumption of meiosis in immature oocytes and release from the ovary are induced by a second mediator, maturation-inducing hormone, identified as 1-methyladenine (1-MeAde) in starfish. The role of GSS is to induce 1-MeAde production by ovarian follicle cells. Thus, GSS was redesignated as gonad-stimulating substance (also GSS). Although GSS has been characterized biochemically as a peptide hormone, the molecular identity had to wait until 2009. Fifty years after the initial finding, GSS was purified from the radial nerve cords of starfish Patiria pectinifera. The purified hormone was a heterodimer composed of A- and B-chains, with disulfide cross-linkages. Based on its cysteine motif, GSS is classified as a member of the insulin/insulin-like growth factor (IGF)/relaxin superfamily. More specifically, phylogenetic sequence analysis revealed that P. pectinifera GSS is a member of the relaxin-type peptide family. Therefore, GSS in starfish has been redesignated as relaxin-like gonad-stimulating peptide (RGP). Subsequently, orthologs of P. pectinifera RGP have been identified in other starfish species, including Asterias amurensis, and Aphelasterias japonica.